The role of reactive oxygen species in the transformation from prostatitis to prostate cancer: a review - Tang, Kaihua; Jiang, Zhipeng; Luo, Wen; Li, Jing; Liang, DeCan; Liu, Lei; Long, ZongMin (Frontiers in Immunology, 2025)
In the study of prostate diseases, the microenvironment associated with chronic prostatitis is characterized by abnormal activation of immune cells, leading to excessive accumulation of pro-inflammatory factors and an imbalance in the antioxidant defense system. This results in the overproduction of reactive oxygen species (ROS) and the subsequent triggering of oxidative stress. Oxidative stress persistently disrupts the homeostasis of prostate tissue through various mechanisms, including the damage to biomacromolecules, the regulation of inflammatory pathways, and the induction of apoptosis. ROS, as natural products of cellular metabolism, exhibit a dual role in biological systems. They are involved in the regulation of physiological signals while also possessing the potential to induce pathological damage. Further research indicates that during the occurrence and progression of prostate cancer (PCa), the gradually increasing ROS in the tumor microenvironment can activate cancer-related signaling pathways, induce Deoxyribonucleic Acid (DNA) mutations, and promote the abnormal proliferation of tumor cells. ROS are widely recognized as pivotal molecules that connect chronic inflammation to carcinogenesis. Currently, the mechanisms by which ROS mediate the cross-linking of inflammatory and carcinogenic signaling pathways during the progression from chronic prostatitis to PCa remain inadequately understood. This review systematically analyzes the multifaceted mechanisms of ROS in inflammation-induced carcinogenesis. It preliminarily elucidates the inflammatory origins of PCa and explores early intervention strategies based on the regulation of oxidative stress. The goal is to provide novel potential targets and a theoretical foundation for the comprehensive prevention and treatment of chronic prostatitis and PCa.